Technological and economical potential of anaerobic-adding raw wastewater-intermittent aeration process for treatment of piggery wastewater - DENG Liang-wei; ZHENG Ping; CHEN Zi-ai (浙江大学学报. 农业与生命科学版)
A technological and economical comparison between the anaerobic-adding raw wastewater-intermittent aeration (Anarwia) process and the anaerobic-Sequencing Batch Reactor (SBR) process and SBR process was carried out. The result of laboratory-and full-scale experiment showed it was not technologically feasible to apply the anaerobic-SBR process to treatment of piggery wastewater because of poor efficiency of pollutant removal from wastewater and higher amount of pollutant remnant in the effluent. The performance of Anarwia process was similar to that of the SBR process, with however more efficient removal of pollutant and relatively lower concentration of pollutant in the effluent, which meet the national wastewater discharge standard. The hydraulic retention time (HRT), investment, sludge yield and oxygen demand for the Anarwia process were respectively 38.6%, 11.8%, 16.4% and 95.9% lower than those for SBR process. During the treatment with the Anarwia process, biogas of 2784 m3/d was produced. If the biogas was not taken into account, the operation cost for the Anarwia process was 47.5% lower than that for the SBR process. If taken into account, the operation cost for the former was only 9.1% of the latter. The technological and economical analysis indicated that Anarwia process is a stable, high-removal, cost-efficient and novel process, and is a prospective substitution for SBR process in treatment of piggery wastewater.